Reorientasi Kurikulum LPTK Profil dan Prospek Guru - Warul Walidin (Universitas Islam Negeri Ar-Raniry, 2001)
There is no doubt that the curriculum should be relevant to the current need of society. This is particularly true in educational institutions, including institutions for Islamic teacher training. This article focused its study on the profile and the prospect of teacher. Imam al-Ghazali insists that a teacher is a good person in malakut world. Al-abrashi writes that a teacher is a spiritual father. This being the case, the institution fo teacher training, through its relevant curriculum, plays a significant role in producing professional teachers who are capable of coping with the rapid development of science, technology, and social changes.